(untitled) (Journal of Scientific Research, 2025)
A simple one-pot synthesis method was used to synthesize reduced graphene oxide (rGO) blended PbS nanocomposite (NC) from Centella asiatica leaf extract. Its photocatalytic and antibacterial properties were studied and compared with that of PbS nanoparticles (NPs) synthesized by precipitation method. PbS with cubic structure was confirmed by XRD studies. With the incorporation of rGO, the size of PbS crystals decreased from 27 nm to 23 nm. For rGO-blended PbS, grain boundaries are well defined and agglomeration is minimised. Pb–S related bands seem to shift towards lower wavenumber side for rGO-PbS NC. PL intensity decreased for rGO-PbS NC due to suppression of recombined photoelectrons and holes. With rGO inclusion, the absorption edge shifted towards higher wavelength, decreasing the band gap. By providing larger surface area, rGO enhanced the photodegradation efficiency of PbS from 84.38 % to 95.06 % against methylene blue (MB)under visible light. Bacterial growth inhibition nature of PbS improved with rGO incorporation.